Employment and satisfaction outcomes from a job retention intervention delivered to persons with chronic diseases. - Allaire SH; Niu J; LaValley MP (Rehabilitation Counseling Bulletin, 2005)
Job retention services are recommended for people with chronic diseases based on their high risk for work disability. This randomized trial tested the effectiveness of a job retention intervention in a sample of employed persons with rheumatic diseases at risk for work disability. One hundred and twenty-two experimental participants received the job retention intervention, and 120 controls received written materials. Employment status was assessed at 6-month intervals up to 48 months after enrollment. Main outcomes were time to job loss and satisfaction with the experimental and control interventions. The log-rank test was used to detect a difference between the groups in time to job loss. Between-group differences in satisfaction scores were analyzed using Wilcoxon tests. Job loss was delayed in experimental participants compared with controls, p = 0.03. Satisfaction scores for the job retention intervention were substantially higher than those for the written materials, p < 0.0001. Job retention intervention has the potential to reduce the high rates of chronic disease-associated job loss.